(untitled) (International relations and international law Journal, 2018)
The interest of China and India in closer relations with Kazakhstan, which is rich in reserves of resources, is evident in Chinese and Indian energy activity in the CA region, is explained by the growing demand for oil from rapidly growing economies. The energy dimension of Kazakhstan’s foreign policy changes the geopolitics of not only Central Asia, but also affects the geopolitics of Asia with the participation of China and India. The authors pay attention to the review of theories of the geopolitics of energy resources with reference to the triangle Kazakhstan – China – India. The study of different points of view on the geopolitical processes in Central Asia with the participation of China and India made it possible to systematize a large amount of research on the country (national) principle and identify problematic issues that have not yet been studied. They analyze regional processes in which energy has become part of geopolitics, affecting the international configuration of Eurasia. Attention is drawn to the strategic intersection of the interests of China and India in Central Asia, examines how India and China compete for energy in Kazakhstan and how far China or India benefits or loses in this energy game in the region. China has specific strategies for its energy security in the region, for example, the mega-project «One belt, one way», involving all the states of Eurasia, including Kazakhstan and India. The authors raise the issue of the possibility of cooperation between the two powers in the energy sector of Kazakhstan in the context of their participation in regional organizations, for example the establishment of the SCO energy club or the Eurasian energy club. The energy prospects of China and India in Kazakhstan/CA are associated with a sustained interest in maintaining stability and security. Key words: energy resources, geopolitics, multi-vector policy of Kazakhstan, China’s energy activities, energy security of India